The role of Cdx genes in the gut and in axial development. (22nd March 2010) - Beck, Felix; Stringer, Emma J.
Abstract : The Cdx ( Caudal -type homeobox) group of ParaHox genes ( Cdx1, Cdx2 and Cdx4 in the mouse) perform multiple functions in mammalian development. Cdx1 is concerned with axial positional information, and its deletion appears to have no important effect other than a disturbance of axial patterning. In contrast, Cdx2 is required for trophoblast differentiation, axial patterning and extension, as well as for morphological specification (i.e. patterning) of gut endoderm. Cdx4 -knockout animals do not present an abnormal phenotype, but, when combined with Cdx2 haploinsufficiency, present a dramatic picture involving abnormal cloacal specification. The latter is probably due in large part to defective paraxial mesodermal development in the caudal region, but may also involve defective endodermal growth. A significant degree of redundancy is apparent between the Cdx genes with respect to caudal extension and possibly also during gut development.